Rechargeable battery modeling and lifetime optimization - El Agroudy, Naglaa (AUC Knowledge Fountain, 2013)
Battery lifetime is one of the most important design considerations in rechargeable battery operated devices. Understanding the battery nonlinear properties is essential for appropriate battery modeling. Optimizing the battery lifetime depends greatly on the discharge current profile. Changing the profile shape can be done through averaging techniques, scheduling techniques, introducing recovery periods, etc. This work investigates the different techniques that can be used to enhance the battery lifetime. It is shown that 15-60% of lifetime savings can be achieved through using average current profile instead of variable current profile. This work also provides a comparison between different configuration techniques for multi-cell systems. Also, a new hybrid battery model is introduced which combines the battery electric circuit characteristics together with the nonlinear battery properties.